Overexpression of BMI1, a Polycomb Group Repressor Protein, in Bladder Tumors: a Preliminary Report - Malekzadeh Shafaroudi, Afsaneh; Mowla, Seyed Javad; Ziaee, Seyed Amir-Mohsen; Bahrami, Ahmad-Reza; Atlasi, Yaser; Malakootian, Mahshid (Urology Journal, 2008)
Introduction: A Polycomb group repressor protein named BMI1 represses the genes that induce cellular senescence and cell death, and it can contribute to cancer when improperly expressed. We aimed to evaluate expression of BMI1 gene in bladder tumors. Materials and Methods: Tissue specimens containing bladder tumor were evaluated and compared with intact tissues from tumor margins and normal bladders. There were 40 tumor specimens of patients with transitional cell carcinoma of the bladder, 20 tumor-free tissues taken from the margin of the tumors, and 8 specimens from patients without tumor. Specific primers for BMI1 and B2M (as an internal control) were used for reverse transcript polymerase chain reaction technique. The production and distribution of BMI1 protein was also examined by western blotting and immunohistochemistry techniques. Results: Polymerase chain reaction generated a 683-bp product, corresponding to the expected size of BMI1 amplified region. The identity of the amplified fragment was then confirmed by direct DNA sequencing. The mean of expression of BMI1 detected in tumor tissues was significantly higher than that in intact tissues, and there was also a significant association between the mean of gene expression and the stage of malignancy (P < .001). The expression of BMI1 at protein level was further confirmed by western blotting and immunohistochemistry. Conclusion: BMI1 is a potent repressor of retinoblastoma and p53 pathways, and hence, elucidating its role in tumorigenesis is very important. We reported for the first time the expression of BMI1 and its correlation with incidence and progress of bladder tumors.